(untitled) (Physical Education, Health and Social Sciences, 2025)
Introduction: Patient satisfaction with nursing care is a critical indicator of healthcare quality, reflecting how content patients are with the care they receive from nurses. This satisfaction is influenced by various factors, including patient characteristics, expectations, and the quality of nursing interactions. Studies show that high-quality nursing care not only improves health outcomes but also enhances patient loyalty and the reputation of healthcare institutions. Nurses, who are often the primary point of contact for patients, play a pivotal role in shaping patient experiences through effective communication, empathy, and involvement in care decisions. This study employed a descriptive cross-sectional design to assess the relationship between various factors affecting patient satisfaction with nursing care. It targeted admitted patients in a public hospital in Charsadda. A sample of 385 patients was determined using a Raosoft online calculator. Convenience sampling was used to select participants due to its accessibility and ease of implementation. The research was conducted from August 25 to November 30, 2024. Descriptive and inferential statistics were used for data analysis. Overall, patients reported moderate satisfaction with nursing care. The highest satisfaction levels were for courtesy and respect (37.4%), teamwork (38.2%), and overall nursing quality (40.5%). The lowest satisfaction was related to patient privacy (4.4%), noise levels (8.1%), and those who visited only once. Satisfaction levels were similar for both genders, with male patients slightly more likely to report higher satisfaction. This study highlights the crucial role of nursing care in shaping patient satisfaction, with factors such as effective communication and teamwork significantly enhancing patient experiences. The findings underscore the importance of addressing these gaps to improve overall care quality and meet patient expectations in healthcare settings.